2008
DOI: 10.1530/rep-07-0340
|View full text |Cite
|
Sign up to set email alerts
|

Murine SPAM1 is secreted by the estrous uterus and oviduct in a form that can bind to sperm during capacitation: acquisition enhances hyaluronic acid-binding ability and cumulus dispersal efficiency

Abstract: Sperm uptake of epididymal sperm adhesion molecule 1 (SPAM1) in vitro has recently been shown to be a marker of sperm maturation, since acquisition of this surface hyaluronidase increases cumulus dispersal efficiency. Here, we demonstrate that this glycosyl phosphatidylinositol-linked sperm antigen, previously shown to be expressed during estrous in the female reproductive tract, is secreted in the uterine and oviductal fluids (ULF and OF respectively) in a 67 kDa form, which can bind to sperm. We show that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 39 publications
4
49
0
1
Order By: Relevance
“…Clusterin, and other lipid carriers such as APOA1, serve as GPI-linked protein monomer stabilizers, donors to the sperm plasma membrane (PM), and as acceptors of cholesterol. This interesting datum was confirmed by the finding that when Spam1 -/-were exposed to accessible Spam1 there was a significant difference in cumulus dispersal efficiency (Griffiths et al, 2008), thus suggesting that the sperm surface remodeling occurring prior to and during capacitation could involve the functional expression of Spam1, in an integrated cross-talk between male and female structures. This specific peculiarity, could explain the fertility of Spam1 -/-mice.…”
Section: Discussionmentioning
confidence: 69%
“…Clusterin, and other lipid carriers such as APOA1, serve as GPI-linked protein monomer stabilizers, donors to the sperm plasma membrane (PM), and as acceptors of cholesterol. This interesting datum was confirmed by the finding that when Spam1 -/-were exposed to accessible Spam1 there was a significant difference in cumulus dispersal efficiency (Griffiths et al, 2008), thus suggesting that the sperm surface remodeling occurring prior to and during capacitation could involve the functional expression of Spam1, in an integrated cross-talk between male and female structures. This specific peculiarity, could explain the fertility of Spam1 -/-mice.…”
Section: Discussionmentioning
confidence: 69%
“…It has been found to be secreted in the female reproductive tract (including the oviduct) and it can bind to sperm (Griffiths et al 2008). It was shown that hyaluronic acid interacts with the R4 S Ghersevich and others PH-20 protein anchored on the macaque and human sperm membrane increasing the basal levels of intracellular calcium and promoting the induced acrosome reaction (Sabeur et al 1998, Cherr et al 1999.…”
Section: Sperm Adhesion Molecule 1 (Spam1)mentioning
confidence: 99%
“…During post-testicular maturation of sperm, a variety of glycosyl phosphatidylinositol (GPI)-linked proteins are added to the surface of the sperm as they traverse the male and female tract [1][2][3]. These proteins include receptors and immunoprotection molecules, as well as enzymes that participate in both sperm maturation and the fertilization processes [2,3].…”
Section: Introductionmentioning
confidence: 99%